Response of Growth and Production of Pare (momordica charantia L) to Dosage of Organic Liquid Fertilizer and Various Organic Mulch - Muhammad Arief; Iswahyudi Iswahyudi; Yenni Marnita (University of Prof. Dr. Hazairin, SH, 2022)
This study aims to see the response to the growth and yield of bitter melon plants due to the administration of NASA liquid organic fertilizer doses and various organic mulches, as well as to see the interaction between liquid organic fertilizer doses and various organic mulches. This research was conducted in Paya Bujok Beuramo Village, West Langsa District, Langsa City. The research time was 3 months, starting from June to August 2021. This study used a factorial randomized block design (RAK), which consisted of 2 factors, namely: The first factor was liquid organic fertilizer dose (N), consisting of 4 factors, namely: N0 = control, N1 = 2 ml/plot N2 = 2.4 cc/plot and N3 = 2.8 ml/plot and the second factor is various organic mulch (M) which consists of 3 levels, namely: M1 = Rice straw (1.8 kg/plot), M2 = Sawdust (1.8 kg/plot) and M3 = Alang-alang (1.8 kg/plot). The parameters observed were plant height, fruit length, fruit diameter, and fruit weight per plant. The results showed that the dosage of liquid organic fertilizer significantly affected the parameters of plant height, fruit length, fruit diameter, and fruit weight per plant. The best results were obtained in the treatment of N3 (dose of 2.8 ml/plot). The application of various organic mulches significantly affected the parameters of plant height, 1st and 2nd harvest length, 1st harvest fruit diameter, and fruit weight per plant. The best results were obtained in the M1 treatment (rice straw mulch). The interaction of liquid organic fertilizer dose treatment with various organic mulches had a significant effect on plant height parameters at 30 and 45 DAP, as well as fruit weight parameters per 1st harvest plant. The best interaction was obtained in the treatment combination N3M1. (dose of 2.8 ml/plot with rice straw mulch)